PENCEGAHAN TINDAK PERUNDUNGAN (BULLYING) DI LINGKUNGAN SEKOLAH MENEGAH ATAS - Muhammad Husni Ingratubun; Fransiscus X. Watkat; Muhammad Hafiz Ingsaputro; Muhammad Toha Ingratubun (LPPM Universitas Bina Bangsa, 2024)
Bullying is a social phenomenon that is increasingly occurring in children's social circles these days, including in the social circles of children in high schools. This social phenomenon, if left unchecked, will have a bad or negative impact on the growth and development of children as the next generation of the ideals of the Indonesian nation's struggle. Through this Community Service Program (CSP), it is hoped that it can provide enlightenment to students, teachers and educational staff within thei Senior High School Negeri 2 Sentani, Jayapura Regency, Province of Papua about various matters related to the issue of bullying. The method used in this activity is the counseling and discussion method. CSP is expected to provide output results that match the ultimate goal of implementing CSP, namely creating a school environment free from bullying behavior